PENGARUH KUALITAS FRAUD BRAINSTORMING SESSIONS TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI FRAUD DI LAPORAN KEUANGAN (Studi Empiris pada KAP di Semarang) - Laksana, Anggit Chandra; Achmad, Tarmizi (Diponegoro Journal of Accounting, 2020)
This study aims to examine and determine the effect of fraud brainstorming sessions quality on the auditor's ability to detect fraud in financial statements. The sample used in this study was the auditor who worked on KAP in Semarang with a total of 68 respondents from 13 KAP. This study uses primary data in the form of answers to questionnaires given to respondents and uses purposive sampling method in the process of sampling. The analysis technique used in testing hypotheses is linear regression analysis. The results of this study indicate that the quality of fraud brainstorming sessions has a significant positive effect on auditor's ability to detect fraud in financial statements. This research shows that the higher the quality of fraud brainstorming sessions will increase the auditor's ability to detect fraud in financial statements.